2015
DOI: 10.1002/admi.201500192
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up Generation of Miniaturized Coaxial Double Electrodes with Tunable Porosity

Abstract: effi cient electrochemical devices, particularly in the fi eld of implantable biofuel cells and biosensors. Among other parameters, the diffusion and redox reaction of molecules such as oxygen determines the operating voltage and thus the effi ciency of oxygen-dependent biofuel cells. [ 25,26 ] The present work introduces a new and straightforward strategy for the bottom-up fabrication of a miniaturized coaxial electrode architecture based on highly organized porous gold as a structural material with controlla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…All experiments were performed with bare and smooth carbon fibers which can explain the leaking of the redox polymers. Therefore, the use of more sophisticated porous and cylindrical electrodes in combination with our bioelectrocatalysts would be the perfect candidates to optimize the BFC (Karajic et al, 2015). The porosity will offer high specific surface to improve the current while maintaining the geometric surface area and will also allow retaining the polymer and protecting the hydrogel within its structure.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed with bare and smooth carbon fibers which can explain the leaking of the redox polymers. Therefore, the use of more sophisticated porous and cylindrical electrodes in combination with our bioelectrocatalysts would be the perfect candidates to optimize the BFC (Karajic et al, 2015). The porosity will offer high specific surface to improve the current while maintaining the geometric surface area and will also allow retaining the polymer and protecting the hydrogel within its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Five porous gold‐coated electrodes made of 5, 7, 11, 15 and 19 half‐layers ( HL ) of pores were manufactured according to a three‐step procedure . An organized colloidal template of silica beads of diameter ds=p=1.17 μm was first deposited on a gold wire of radius R 1 =125 μm, using the Langmuir‐Blodgett technique and controlling the number of bead layers ,.…”
Section: Application Of the Macroscopic Modelmentioning
confidence: 99%
“…In the recent past decades, porous electrodes, which are of major interest for the design of miniaturized electro‐devices such as bio‐batteries or bio‐sensors, have recieved considerable attention both from modeling and experimental points of view . A well‐defined pore size and pore distribution of the porous material may be achieved by using the Langmuir‐Blodgett templating technique, providing a high surface‐to‐volume ratio (specific area) ,. Such a feature allows the electrodes to produce much higher electrical current per unit volume than classical flat electrodes of the same macroscopic size .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, different technologies have been explored to downscale the dimensions of such devices. Fabrication of electrochemical platforms has been largely supported by screen‐printing, photolithography, and electrodeposition techniques that were widely used for the design of miniature devices such as micro‐batteries, micro‐fuel cells, micro‐supercapacitors, electroanalytical systems, and nanofluidic devices (e.g. for biodetection, redox cycling for single‐molecule electrochemistry in femtoliter volumes etc.)…”
Section: Figurementioning
confidence: 99%
“…In previous work, we have demonstrated that a fully integrated miniaturized electrochemical cell can be elaborated based on a bottom‐up approach, leading to a coaxial arrangement of two macroporous microelectrodes. The use of the Langmuir–Blodgett (LB) technique in the elaboration process permits us to precisely tune the inter‐electrode distance.…”
Section: Figurementioning
confidence: 99%